ADB support for the sustainable development goals enabling the 2030 agenda for sustainable development through strategy 2030. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The report draws on project examples to highlight how ADB operations contribute to clusters of interconnected SDGs related to people, planet, prosperity, and sustainable infrastructure. It also details ADB efforts to help developing member countries mobilize the finance and knowledge necessary to achieve the SDGs.
Keywords: Sustainable development; Electronic book